Measuring user emotional responses using Geneva Emotion Wheel towards learning management systems - Wan Nooraishya Wan Ahmad; Ahmad Rizal Ahmad Rodzuan; Voon Mei Luan (Institute of Advanced Engineering and Science, 2022)
The learning management system (LMS) has been used widely in higher learning institutions for blended learning; this interaction involves user cognition and may induce emotional experience. Therefore, the user has to sustain a positive emotional experience towards using LMS to avoid difficulty in the learning process. However, the user emotions and the design elements that induced the emotions are yet to discover. This study aims to analyse user emotional responses to a learning management design and examine the emotional design features of a learning management system. Two versions of a higher learning institution LMS were used and investigated using Geneva Emotion Wheel (GEW). The findings show that both LMS versions lack-in activate the positive emotions, but prove the LMS designs reduce the activation of negative emotions. Furthermore, the emotional design elements that concern an LMS is explained.